2022
DOI: 10.1001/jamasurg.2022.4457
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation Therapy for All Elderly Patients With Locally Advanced Rectal Cancer?

Abstract: Although the safety of rectal cancer surgery in very carefully selected elderly patients has been established, 1 data on the safety and efficacy of chemoradiation therapy in this patient population is limited. This may explain the relative underuse of radiation therapy in elderly individuals, first noted in 2001. 2 Nassoiy et al, 3 using the National Cancer Data Base in a multicenter retrospective design, demonstrate that only 58.8% of patients older than 80 years diagnosed with a locally advanced rectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The Lyon R 90-01 clinical trial found that pCRT increased the rate of pCR or near-pCR from 10.3% at two-week intervals to 26% at six to eightweek intervals. As a result, the optimal interval between CRT and surgery is currently considered to be six to eight weeks to improve pCR rates and reduce postoperative complications [28,29]. Despite encouraging results from trials that have extended the time between pCRT and surgery, there is still no definitive consensus on the time between the completion of pCRT and surgery, with current studies showing a cautious trend towards delaying surgery.…”
Section: Interval Between Radiation and Surgerymentioning
confidence: 99%
“…The Lyon R 90-01 clinical trial found that pCRT increased the rate of pCR or near-pCR from 10.3% at two-week intervals to 26% at six to eightweek intervals. As a result, the optimal interval between CRT and surgery is currently considered to be six to eight weeks to improve pCR rates and reduce postoperative complications [28,29]. Despite encouraging results from trials that have extended the time between pCRT and surgery, there is still no definitive consensus on the time between the completion of pCRT and surgery, with current studies showing a cautious trend towards delaying surgery.…”
Section: Interval Between Radiation and Surgerymentioning
confidence: 99%
“…The Interval Between Neoadjuvant Therapy and Surgery in the Treatment of Locally Advanced Rectal Cancer (CRONOS) study is a large multi-institutional retrospective analysis across several large hospitals in Spain. The authors should be commended on their effort and collaboration to bring together investigators across several large institutions and an impressive database of over 1500 patients.…”
mentioning
confidence: 99%
“…Though important, the application of the conclusions of this article in the modern era of total neoadjuvant therapy (TNT) is unclear. Over the last decade, TNT is becoming more popular as the treatment of choice for locally advanced rectal cancer with the goal of higher rates of pathologic complete response .…”
mentioning
confidence: 99%
See 2 more Smart Citations